What impact does dialysis have on the patient’s life and mental health? - Kułakowska, Aleksandra; Kuc, Monika; Lepczyński, Bartłomiej; Kłakowicz, Philip; Lechowski, Sebastian (Journal of Education, Health and Sport, 2023)
This essay looks into the effects of dialysis on patients’ mental health and quality of life at the Department of Nephrology. We now live in a period when patients’ mental health is receiving an increasing amount of attention in addition to their physical health. The progression of chronic kidney disease and how it is treated greatly affect the quality of life for dialysis users. Renal insufficiency consequently causes significant restrictions on patients’ ability to engage in social, intellectual, and physical activities. Renal replacement therapy prolongs the lives of people with chronic kidney disease.